Algorithms for Calculating the Indices Determining the Production Efficiency of Swine Breeding Herds: Pigs Weaned Per Sow Per Year and Litters Per Sow Per Year - Saran Parisutthikul; Supat Faarungsang; Monchai Duangjinda; Amara Thongpan (Agriculture and Natural Resources, 2010)
This research aimed to develop algorithms for calculating some important indices that determine the reproductive and production efficiency of swine breeding herds. Algorithms were developed for litters per mated female per year (LMFY) and pigs weaned per mated female per year (PWMFY). Both algorithms can be used to develop an information system for swine breeding herd management by using open source software. The open source software used in this research was XAMPP for Linux. The data used for testing came from the database of PigLive program from a swine farm in Nakornpathom province. The data consisted of two tables containing details on status and history, with 407 and 6,526 records, respectively. The data was imported into the new system that had been developed using a webbased system. Though the comparison of the indices did not agree exactly with the ones reported from the PigLive program based on monthly periods, the values obtained were similar with the same trends. The algorithm developed had five steps: 1) date management, 2) calculation of production, 3) data management to calculate an average mated female inventory (AMFI), 4) calculation formula and 5) presentation of the results.